Glutamate Neurocircuitry: Theoretical Underpinnings in Schizophrenia - Schwartz, Thomas L.; Sachdeva, Shilpa; Stahl, Stephen M. (Frontiers in Pharmacology, 2012)
The Dopamine Hypothesis of Schizophrenia is actively being challenged by the NMDA Receptor Hypofunctioning Hypothesis of Schizophrenia. The latter hypothesis may actually be the starting point in neuronal pathways that ultimately modifies dopamine pathways involved in generating both positive and negative symptoms of schizophrenia postulated by the former hypothesis. The authors suggest that even this latter, NMDA receptor-based, hypothesis is likely too narrow and offer a review of typical glutamate and dopamine-based neurocircuitry, propose genetic vulnerabilities impacting glutamate neurocircuitry, and a provide a broad interpretation of a possible etiology of schizophrenia. In conclusion, there is a brief review of potential schizophrenia treatments that rely on the etiologic theory provided in the body of the paper.